Effect of integrated nutrient management on nutrients availability and uptake by black henbane (Hyoscyamus niger L.) in Tarai region of Uttarakhand - R K Pal, C S Pandey, A K Gupta, H V Puranik, (Journal of Spices and Aromatic Crops, 2014)
Experiments were conducted to quantify the effect of integrated nutrient management on soil health and black henbane (Hyoscyamus niger L.). The treatments were, no chemical fertilizer and organic manure (control) [T1], recommended (rec.) NPK (i.e. 100:50:50 kg ha-1) [T2], 75% rec. NPK +2.5t vermicompost (VC) [T3], 50% rec. NPK + 5.0t VC (T4), 25% rec. NPK + 7.5t VC (T5), VC 10t (T6), rec. NPK + Biofertilizers (BF) [T7], 75% rec. NPK + 2.5t VC + BF (T8), 50% rec. NPK + 5.0t VC + BF (T9), 25% rec. NPK + 7.5t VC + BF (T10), 10t VC + BF (T11) and BF [Azotobacter & Phosphorus Solublizing Bacteria (PSB)]. Highest herbage yield was obtained with application of T8 during both the years. Integrated application of inorganic fertilizers and organic sources of nutrients increased the N, P, K content and their uptake. Highest available N and K content in soil was observed with T2 during 2008–09, while during 2009–10, the maximum available N content in soil was observed with T8. Highest N uptake was observed with T6, while highest P and K uptake was recorded with T8 during both the years.